2017
DOI: 10.15230/scsk.2017.43.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, Anti-wrinkle and Whitening Effect of Fermented Extracts of Hwangryunhaedoktang

Abstract: Hwangryunhaedoktang (HHT) has been traditionally used as a preventive and therapeutic medicine to treat enervation and diverse chronic diseases. This study was designed to compare the antioxidant, anti-wrinkle and whitening effects of HHT extract and its fermented extract by Leuconostoc mesenteroides (FHHT). FHHT was prepared by inoculation of L. mesenteroides after the extraction procedure with 70% ethanol. HHT and FHHT was investigated via high-performance liquid chromatography (HPLC). Simultaneous qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 1 publication
0
0
0
2
Order By: Relevance
“…In 2019, it was reported that the types of pharmacopuncture most commonly used were bee venom (30.5%), followed by blood stasis (18.9%), HHT (7.9%), and ginseng (7.5%) 13 . HHT is composed of four medical herbs: Rhizoma coptidis , Radix scutellariae , Cortex phellodendri , and Fructus gardeniae 15 . In oriental medicine, the components have been believed to produce anti-inflammatory, anti-allergic, anti-bacterial, and antiviral effects 16 .…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, it was reported that the types of pharmacopuncture most commonly used were bee venom (30.5%), followed by blood stasis (18.9%), HHT (7.9%), and ginseng (7.5%) 13 . HHT is composed of four medical herbs: Rhizoma coptidis , Radix scutellariae , Cortex phellodendri , and Fructus gardeniae 15 . In oriental medicine, the components have been believed to produce anti-inflammatory, anti-allergic, anti-bacterial, and antiviral effects 16 .…”
Section: Discussionmentioning
confidence: 99%
“…하이드록시산(hydroxyl acid, HA)은 화장품에서 각질 박리제로 서 많이 사용되는 성분으로, 글라이콜릭산(glycolic acid)을 주성분으 로 하는 알파하이드록시산(alpha hydroxy acid, AHA)과 살리실산 (salicylic acid)인 베타하이드록시산(beta hydroxy acid, BHA)이 있 다 (Bashir et al, 2005 (Tang & Yang, 2018 (Grimes et al, 2004;Kim & Choi, 2018 (Edison et al, 2004;Tasic-Kostov et al, 2010 (Tesfaye et al, 2002 (Kim & Kim, 2015;Park et al, 2019 (Song et al, 2020: Tsukahara et al, 2009. 황기, 동충화초 등을 발효배양하여 미생물의 효소를 이용하여 유기물을 분 해 및 변화시켜 이화학적 특징을 가지는 연구가 보고되었다 (Um et al, 2017;Ahn et al, 2013 (Pervez et al, 2014;Pinto et al, 2015 About 160 μL of various concentrations (from 0.25% to 2%) of 0.2% lactobionic acid solution and F-PHA were added to 40 μL of 1 mM DPPH solution. The plate was incubated for 30 min at ambient temperature, and the absorbance was recorded at 490 nm using a spectrophotometer.…”
Section: Introductionunclassified
“…피부 각질층의 수분량에 관한 선행연구들로는 계절, 연령, 성별 [9][10][11][12] , 환경 13 )에 따른 수분량 연구, 인종에 따 른 연구 [14][15][16][17] , 보습제 [18][19] , 마사지 [20][21] , 매선요법 22) , 고 주파기기 관리 23) , 화장품 [24][25] [28][29][30] . 박 31) , 최 32) , 엄 33) , 김 34…”
unclassified